2005
DOI: 10.1111/j.1460-9592.2005.01773.x
|View full text |Cite
|
Sign up to set email alerts
|

The revised FLACC observational pain tool: improved reliability and validity for pain assessment in children with cognitive impairment

Abstract: Findings support the reliability and validity of the FLACC as a measure of pain in children with CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
245
0
20

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(281 citation statements)
references
References 33 publications
1
245
0
20
Order By: Relevance
“…As evaluated by Malviya S et al, the FLACC scale can be individualized for use in children with altered cognitive states. 12 Nilsson S et al showed that FLACC scale is adequate for children between 5 and 16 years of age. 14 Voepel-Lewis T et al validated the use of FLACC in intensive care units, with a good correlation with numeric 0-10 scales.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As evaluated by Malviya S et al, the FLACC scale can be individualized for use in children with altered cognitive states. 12 Nilsson S et al showed that FLACC scale is adequate for children between 5 and 16 years of age. 14 Voepel-Lewis T et al validated the use of FLACC in intensive care units, with a good correlation with numeric 0-10 scales.…”
Section: Resultsmentioning
confidence: 99%
“…4,9,10 Scales were developed and validated due to theses difficulties, and their use is now well established for the evaluation and intervention on pediatric pain. [9][10][11][12][13][14][15][16][17][18] The implementation of scales has already shown to be plausible and effective on intensive care units, both adult and pediatric. Mansouri P et al demonstrated a decrease of 3 days in ICU stay with the use of protocols and scales for analgesia and sedation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 To address this, the Pediatric Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (Ped-IMMPACT) group has called for "specific planning and co-ordination" for communicating with non-verbal and/or cognitively impaired children. 25,26 The revised FLACC observational tool has been studied and found to be reliable and valid in children with cognitive impairment in some settings, and while challenging to apply in the ED, may provide a starting point for development of a tool in this environment. This underscores the importance of directing educational initiatives for residents on the assessment of pain in non-verbal, developmentally disabled children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the next iteration of the OUCH card will include the revised Face, Leg, Activity, Cry, Consolability Scale observational pain tool, which shows improved reliability and validity for pain assessment in children with cognitive impairment. 39 Finally, determining best practices for the most efficient and cost-effective means of delivering pain management education is a greatly needed step 40 that may be discernible in subsequent studies. The effect of lecture versus OUCH card distribution (as well as their combination) merits further investigation in order to better understand the optimal content and format of training programs.…”
Section: Discussionmentioning
confidence: 99%